2013
DOI: 10.3892/etm.2013.1311
|View full text |Cite
|
Sign up to set email alerts
|

miR-31 promotes oncogenesis in intrahepatic cholangiocarcinoma cells via the direct suppression of RASA1

Abstract: MicroRNAs (miRNAs) are involved in the pathogenesis of intrahepatic cholangiocarcinoma (ICC). However, the role of microRNA-31 (miR-31) in ICC has yet to be elucidated. In this study, we demonstrated that the expression of miR-31 was significantly upregulated in ICC tissues and the human ICC cell line HCCC-9810, when compared with that in normal adjacent tissues. Bioinformatic analysis and a dual-luciferase reporter assay revealed RAS p21 GTPase activating protein 1 (RASA1) to be a direct target of miR-31 in H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(28 citation statements)
references
References 34 publications
0
28
0
Order By: Relevance
“…Of these 18 targets, RASA1 (p120RasGAP) was of particular interest because it functions as a negative regulator of RAS pathway activation and modulates invasion-behavior through interaction with p190RhoGAP (24, 25). Moreover, RASA1 was demonstrated to be a miR-31 target in colorectal and liver cancers (26, 27). The RASA1 3′ UTR contains one predicted miR-31 binding site which is highly conserved in vertebrates (Figure 5A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of these 18 targets, RASA1 (p120RasGAP) was of particular interest because it functions as a negative regulator of RAS pathway activation and modulates invasion-behavior through interaction with p190RhoGAP (24, 25). Moreover, RASA1 was demonstrated to be a miR-31 target in colorectal and liver cancers (26, 27). The RASA1 3′ UTR contains one predicted miR-31 binding site which is highly conserved in vertebrates (Figure 5A).…”
Section: Resultsmentioning
confidence: 99%
“…Multiple miRNA profiling studies have documented the upregulation of miR-31 in pancreatic cancer cell lines and tumors (17, 26, 29, 30). We have found that miR-31 is moderately to highly expressed in 16 of 23 pancreatic and colorectal cancer cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…RASA1 inhibits RAS-induced transformation by functioning as a negative regulator of RAS by promoting the inactive GDP-bound form of RAS (29). It was previously reported that miR-31 targets RASA1 in intrahepatic cholangiocarcinoma and colorectal cancer (39,40), but whether miR-31 targeted it in the lung was unknown. The SPRED and SPRY genes FBS and penicillin/streptomycin.…”
Section: Discussionmentioning
confidence: 99%
“…Most of these microRNAs play a role in cell-cycle control and proliferation. For example, Hu et al found upregulated miR-31 expression in cholangiocarcinoma cells causing altered RAS/MAPK signaling [82]. Other investigators reported on a role for miR-138 in regulating cholangiocarcinoma proliferation, cell-cycle control, and migration, possibly by direct regulation of RhoC [83].…”
Section: Biliary Treementioning
confidence: 97%